Réponses

2013-10-23T16:25:10+02:00
A= 7/5 -7/3x15/14= \frac{7}{5} - \frac{7}{3} * \frac{15}{14} = \frac{7}{5} - \frac{5}{2} = \frac{14-25}{10} = \frac{-11}{10}

B=8/5-3/4 / 9/8= \frac{ \frac{8}{5} - \frac{3}{4} }{ \frac{9}{8} } =  \frac{32-15}{20}* \frac{8}{9} = \frac{17}{5}* \frac{2}{9} = \frac{34}{45}

C=8/3-2/5   /   7/5= \frac{ \frac{8}{3}- \frac{2}{5} }{ \frac{7}{5} } = \frac{ \frac{40-6}{15} }{ \frac{7}{5} } = \frac{34}{15} * \frac{5}{7} = \frac{34}{21}
2013-10-23T16:34:36+02:00
A= 7/5-7/3x15/14
A= 7/5 - 105/42
A=294/210 - 525/210
A=-231/210
A= -11/10

B=8/5-3/4 / 9/8
B=8/5 - 24/36
B=168/180
B=14/15

C=8/3-2/5   /   7/5
C=8/3 - 10/35
C= 250/105
C=50/21